Dietary pyrroloquinoline quinone hinders aging progression in male mice and D-galactose-induced cells - Mohamad Ishak, Nur Syafiqah; Kikuchi, Midori; Ikemoto, Kazuto (Frontiers in Aging, 2024)
Background: Understanding and promoting healthy aging has become a necessity in the modern world, where life expectancy is rising. The prospective benefits of the antioxidant pyrroloquinoline quinone (PQQ) in healthy aging are promising. However, its role in aging remains unclear. Thus, this study aimed to investigate the effect of PQQ on preventing the progression of aging and to explore its underlying molecular mechanisms. Methods: Naturally aged C57BL/6J male mice were fed a normal diet with or without PQQ (20 mg/kg/day) for 10 weeks. Body composition was measured by bioimpedance at weeks 0 and 8. The integument conditions were evaluated at weeks 0, 4, and 8. Muscle strength and function were examined at week 8. At the ninth week, computed tomography images of the mice were captured, and blood and tissue samples were collected. The levels of inflammatory cytokines in the gastrocnemius muscle were measured, and the muscle fiber cross-sectional area in the soleus muscle was examined. Additionally, a D-galactose (D-gal)-induced cell aging model was used to study the effects of PQQ intervention on cell proliferation, senescence, differentiation, ROS levels, and mitochondrial function in myoblasts (C2C12). Cell proliferation and monolayer permeability of D-gal-induced intestinal epithelial cells (IEC6) were also examined. Results: Aged mice suffered from malnutrition; however, PQQ supplementation ameliorated this effect, possibly by improving metabolic dysfunction and small intestinal performance. PQQ prevented rapid loss of body fat and body fluid accumulation, attenuated muscle atrophy and weakening, reduced chronic inflammation in skeletal muscles, and improved skin and coating conditions in aged mice. Furthermore, PQQ intervention in D-gal-treated C2C12 cells improved mitochondrial function, reduced cellular reactive oxygen species (ROS) levels and senescence, and enhanced cell differentiation, consequently preventing age-related muscle atrophy. In addition, PQQ increased cell proliferation in D-gal-treated IEC6 cells and consequently improved intestinal barrier function. Conclusion: PQQ could hinder the aging process and particularly attenuate muscle atrophy, and muscle weakness by improving mitochondrial function, leading to reduced age-related oxidative stress and inflammation in muscles. PQQ may also ameliorate malnutrition caused by intestinal barrier dysfunction by enhancing IEC proliferation. This study provides evidence for the role of PQQ in aging and suggests that PQQ may be a potential nutritional supplementation that can be included in healthy aging strategies.